Lekarze oraz sposoby leczenia cholery w czasie epidemii w Wielkiej Brytanii w latach 1831-1832 - Straszak-Chandoha, Sylwia (Doctor's and cholera's ways of treatment during the epidemy in Great Britain 1831-1832, 2007)
The article presents the medical environment of the 19lh century in England, particularly the methods of the treatment of cholera which were known and employed in those times. The main problem with cholera’s treatment was the lack of knowledge about the origins of this plague. Without knowledge of causes and ways of proliferation of the disease the attempt at isolating the sick, cleaning and disinfection of premises had to failed. The ways of treatments as well as availability of medicines were not accessible to medical profession of the 19th century England.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 136-156